Collateral status affects the onset-to-reperfusion time window for good outcome. Issue 9 (8th March 2018) - Kim, Byung Moon; Baek, Jang-Hyun; Heo, Ji Hoe; Nam, Hyo Suk; Kim, Young Dae; Yoo, Joonsang; Kim, Dong Joon; Jeon, Pyoung; Baik, Seung Kug; Suh, Sang Hyun; Lee, Kyung Yol; Kwak, Hyo Sung; et al.
Abstract : Objective: To characterise the time window in which endovascular thrombectomy (EVT) is associated with good outcome, and to test the differential relationship between functional outcome and onset-to-reperfusion time (ORT), depending on collateral status. Methods: This was a retrospective analysis of clinical and imaging data of 554 consecutive patients, who had recanalisation success by EVT for anterior circulation large artery occlusion, from the prospectively maintained registries of 16 comprehensive stroke centres between September 2010 and December 2015. The patients were dichotomised into good and poor collateral groups, based on CT angiography. We tested whether the likelihood of good outcome (modified Rankin Scale, 0–2) by ORT was different between two groups. Results: ORT was 298 min±113 min (range, 81–665 min), and 84.5% of patients had good collaterals. Age, diabetes mellitus, previous infarction, National Institutes of Health Stroke Scale, good collaterals (OR 40.766; 95% CI 10.668 to 155.78; p<0.001) and ORT (OR 0.926 every 30 min delay; 95% CI 0.862 to 0.995; p=0.037) were independently associated with good outcome. The drop in likelihood of good outcome associated with longer ORT was significantly faster in poor collateral group (OR 0.305 for every 30 min; 95% CI 0.113 to 0.822) than in good collateral group (OR 0.926 for every 30 min; 95% CI 0.875 to 0.980). Conclusions: Earlier successful recanalisation was strongly associated with good outcome in poor collateral group; however, this association was weak during the tested time window in good collateral group. This suggests that the ORT window for good outcome can be adjusted according to collateral status.